Smart edible coating films based on chitosan and beeswax–pollen grains for the postharvest preservation of Le Conte pear. Issue 16 (3rd March 2021) - Sultan, Maha; Hafez, Omaima M.; Saleh, Malaka A.; Youssef, Ahmed M.
Abstract : Smart edible coating films can be used in food packaging. Abstract : Smart edible coating films can be used in food packaging. For this application, they must have good physical and mechanical properties. Herein, chitosan–beeswax based film is used to preserve Le Conte pears postharvest. The chitosan–beeswax films were characterized using XRD, FT-IR, and SEM analysis. Moreover, all films showed good self-healing aptitudes ranging from 86.7 to 96.3. The film treated with pollen grains showed an enhanced water contact angle compared with the chitosan film. The chitosan–beeswax/pollen grain film exhibited a two-fold lower WVTR value compared to the chitosan film, and showed the tendency to increase the stiffness of the film. The elongation% at break was reduced from 35.81 to 14.09. Fruit quality parameters were determined in cold storage for 105 days during shelf life after a simulated marketing period of 7 days. All coated fruits successfully showed decrease in weight loss, decay and rate of softening. Therefore, chitosan–beeswax/pollen grains can be considered safe and effective coating for the fruit preservation.